On the projection constants of some topological spaces and some applications. (25th November 2001) - El-Shobaky, Entisarat; Ali, Sahar Mohammed; Takahashi, Wataru
Abstract : We find a lower estimation for the projection constant of the projective tensor productX ⊗   ∧ Y and the injective tensor productX ⊗   ∨ Y, we apply this estimation on some previous results, and we also introduce a new concept of the projection constants of operators rather than that defined for Banach spaces.